2014
DOI: 10.1002/gps.4209
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study evaluating the risk of hip fracture among patients with dementia in Taiwan

Abstract: People with dementia experience an increased incidence of hip fracture and are at a higher risk of sustaining a hip fracture in the future. Proper and effective hip fracture-prevention strategies are essential for dementia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The high prevalence of malnutrition in people with dementia could be one of the pathophysiological mechanisms for the high risk of falls and fractures, as well as for their poor functional recovery after a fracture [ 27 , 37 , 42 , 74 ]. People with dementia suffered an increase in incidence of hip fracture, as dementia is a risk factor for hip fracture [ 75 ]. Strategies for the prevention of hip fractures are very important in people with dementia because they present a higher prevalence of complications, higher risk of institutionalization, and worse functional recovery [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of malnutrition in people with dementia could be one of the pathophysiological mechanisms for the high risk of falls and fractures, as well as for their poor functional recovery after a fracture [ 27 , 37 , 42 , 74 ]. People with dementia suffered an increase in incidence of hip fracture, as dementia is a risk factor for hip fracture [ 75 ]. Strategies for the prevention of hip fractures are very important in people with dementia because they present a higher prevalence of complications, higher risk of institutionalization, and worse functional recovery [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several previous studies have demonstrated an increased risk of fractures in dementia patients. [ 11 14 ] The risk of hip fracture was 2.57 times higher in Alzheimer's disease patients than in a control group (95% CI = 2.32–2.84). [ 11 ] Another study described a 1.92 times higher risk of hip fracture in dementia patients, including those with Alzheimer's disease and unspecified dementia (95% CI = 1.48–2.49).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several previous studies have demonstrated an increased risk of hip fractures in dementia patients. [ 11 14 ] However, the association between dementia and other types of fractures, such as distal radius and spine fractures, has rarely been considered in previous studies. Furthermore, only a few studies have evaluated the risk of dementia after fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the study found that falls caused 92% of hospital admissions in this study, with a significantly higher proportion occurring in older adults with dementia than in those without, which is consistent with previous research. 29,30 Transport-related injuries (3.4%) and burns (1.0%) were the next most common reasons for admission to the hospital for an injury.…”
Section: Discussionmentioning
confidence: 99%